Happy feet - Miller, George 1945-; Coleman, Warren; Collee, John 1955-; Morris, Judy 1947-; Wood, Elijah 1981-; Murphy, Brittany 1977-2009; Jackman, Hugh 1968-; Kidman, Nicole 1967-; Weaving, Hugo 1960-; Williams, Robin 1951-2014 (Warner Home Video, 2006)
Emperor Penguins from Antarctica each express their true love with a special heartsong of their own that expresses their very being. However, the misfit Mumble cannot sing. Instead he has an extraordinary talent to tap dance with almost magical energy and expression. Nevertheless, the leadership of the colony fearfully blames the young penguin's unorthodox ways for the lean fishing that threatens them all. Defiant in the face of unjust rejection, Mumble and his true friends set out to find the true cause of the famine. Through the friends trials and perils, Mumble learns many things about his frozen world, not the least of which being that his toe tapping talent may be what he needs to save his people
Animationsfilm. USA, 2006
Title from container
Originally released as a motion picture in 2006
Special features: Two new fully animated additional sequences: "Mumble meets a blue whale" and "A 'Happy feet' moment"; take a private dance lesson with Savion Glover; two music videos: "Hit me up" by Gia and "The song of the heart" by Prince; classic cartoon "I love to singa"; theatrical trailer
Keywords: Emperor penguin / Juvenile drama; Tap dancing / Juvenile drama; Fishing / Catch effort / Antarctica / Juvenile drama; Friendship / Antarctica / Juvenile drama; Antarctica / Juvenile drama; Emperor penguin; Fishing / Catch effort; Friendship; Tap dancing; Antarctica; Action and adventure films; Animated films; Drama; Fantasy films; Juvenile works; Film; DVD-Video